Process Performance of the Arenga Sap Vacuum Evaporator using a Solar Panel as a Single Power Source - Daman Huri; Erwin; Hendra; Slamet Wiyono; Iqbal Maulana (Fakultas Teknik Universitas Pancasila, 2026)
Traditional processing of Arenga sap still faces significant challenges, particularly long heating duration and high energy consumption. This study aims to evaluate the performance and energy efficiency of a solar-powered vacuum evaporator for the concentration of Arenga sap. The solar energy system consists of monocrystalline panels, an MPPT charge controller, a deep-cycle battery, and an inverter as the primary power source for the vacuum pump and induction heater, while thermal insulation is applied to minimize heat loss during evaporation. The performance test was conducted using 40 kg of fresh Arenga sap under a vacuum pressure of –0.71 to –0.73 bar and an operating temperature of 34–41°C for 150 minutes, resulting in 1.10 kg of evaporated mass. Based on the corrected and consistent dataset, the evaporation rate was calculated as 0.44 kg/hour, and the energy analysis using the latent heat of vaporization yielded an overall system efficiency of 83%. The novelty of this research lies in the implementation of a fully solar-powered low-pressure vacuum evaporator equipped with thermal insulation to enhance thermal stability. The findings indicate that this system can operate independently and offers a practical solution for small-scale Arenga sap producers, especially those located in remote or off-grid areas.